Dakwah Islami Dan Edukasi Tahsin Al-Qur'an Bagi Masyarakat : Pengabdian Kepada Masyarakat di Masjid Nurul Huda Cipendawa Cianjur - Mubarok, WIldan Fata; Oki, Alber; Yusfa, Muhammad Adriansyah Maulana; Izzudin, Abdurrahman; Kurnia, Muhammad Naufal Rabbani; Hidayat, Amhar Salim; Saputra, Dino (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2025)
This service aims to develop students' abilities in improving their teaching skills. Teaching to the community as a form of service to the community and religious community. Teaching to the community to help the community in solving unanswered problems in order to form a prosperous society and life lessons for the surrounding community. Student involvement in the process of teaching knowledge to the community is a step towards achieving this goal. This program not only improves the quality of teaching, but also helps to increase students' sense of responsibility towards religion and community, as well as the knowledge that has been achieved during the learning period.